Low-cost outpatient chemotherapy regimen of cisplatin, 5-fluorouracil and leucovorin for advanced head and neck and esophageal carcinomas - Fabrício, Vanessa de Carvalho; Amado, Fernanda; Giglio, Auro Del (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: Patients with advanced head and neck (H/N) and esophageal squamous cell carcinoma (SCC) often have a poor performance status and a dire prognosis. Our aim was to evaluate the feasibility, activity and quality of life (QOL) of an outpatient chemotherapy regimen consisting of cisplatin, 5-fluorouracil and leucovorin (CFL). DESIGN AND SETTING: Prospective phase II study conducted at a Brazilian public institution. METHODS: Fifteen patients with residual, recurrent or metastatic SCC of the H/N or esophagus received bolus infusions of leucovorin 20 mg/m2/day and 5-fluorouracil 370 mg/m2/day on days 1-4, and 90 minutes of infusion of cisplatin 25 mg/m2 /day on days 1-3, every 21 to 28 days, depending on hematological recovery. We also evaluated QOL by applying the European Organization for Research and Treatment of Cancer Quality of Life-C30 questionnaire (EORTC QLQ-C30) before each cycle. RESULTS: The overall response rate was 36%, and the mean overall survival and progression-free survival were six and three months, respectively. We observed grade 3 or higher hematological toxicity in seven patients and one patient had grade 3 nausea and vomiting. One patient died because of neutropenic fever. Seven out of the 12 patients who could be evaluated regarding QOL presented an improvement in their overall health status and functional QOL scores over the course of the treatment. CONCLUSIONS: CFL is an active outpatient protocol with tolerable toxicity and a favorable QOL impact. Larger studies are warranted, in order to confirm these results.